Mindfulness as an intervention after multisystem trauma. (October 2021) - Clement, Elizabeth; Murphy, Patrick; Lee, Anna; Ericson, Austin; Gratton, Carolyn; Clements, Thomas; Ryan, Joanna; Kim, Michael; Ball, Chad G; Widder, Sandy
Background: There is a known significant risk of negative mental health consequences following traumatic injury, yet no standard approach to prevent psychiatric illness in trauma patients currently exists. Mindfulness-based psychotherapies have been shown to reduce symptoms of post-traumatic stress disorder, depression and anxiety and improve resiliency, however it is unknown whether a mindfulness intervention immediately following traumatic injury would lead to diminished mental health consequences. Methods: Multi-system trauma patients at the University of Alberta Hospital (N = 63) and the Foothills Hospital (N = 60) were assigned to the experimental and control groups respectively. Patients in the experimental group were asked to use the guided mindfulness application "Stop, Breathe & Think" for 28 consecutive days. All patients completed the Depression Anxiety Stress Scale (DASS-21) and Connor-Davidson Resilience Scale (CD-RISC) 48 hours and 28 days following admission. An exit interview was conducted for patients in the experimental group. Results: There was no significant difference in mean enrollment DASS-21 scores, mean enrollment CD-RISC scores, mean follow-up DASS-21 scores and mean follow-up CD-RISC scores between experimental and control groups. Paired t-tests of mean admission and mean follow-up DASS-21 and CD-RISC scores were not significantly different in the experimental group. Paired t-tests of mean admission and follow-up CD-RISC scores were not significantly different in the control group whereas mean followup DASS-21 scores were decreased in the control group relative to enrolment DASS-21 scores (p = 0.014). Patients reported improved mood after use of mindfulness, and most planned to continue using the therapy and would recommend it to others. Conclusion: Our study did not demonstrate an objective benefit of mindfulness intervention immediately following traumatic injury. Exit interview data suggests that a web-based mindfulness intervention may be beneficial for certain trauma patients however further research is required to identify those most likely to realize substantial gains.